A modular cell culture device for generating arrays of gradients using stacked microfluidic flows - Sip, Christopher G. (American Institute of Physics, 2011)
Microfluidics has become increasingly important for the study of biochemical cues because it enables exquisite spatiotemporal control of the microenvironment. Well-characterized, stable, and reproducible generation of biochemical gradients is critical for understanding the complex behaviors involved in many biological phenomena. Although many microfluidic devices have been developed which achieve these criteria, the ongoing challenge for these platforms is to provide a suitably benign and physiologically relevant environment for cell culture in a user-friendly format. To achieve this paradigm, microfluidic designs must consider the full scope of cell culture from substrate preparation, cell seeding, and long-term maintenance to properly observe gradient sensing behavior. In addition, designs must address the challenges associated with altered culture conditions and shear forces in flow-based devices. With this consideration, we have designed and characterized a microfluidic device based on the principle of stacked flows to achieve highly stable gradients of diffusible molecules over large areas with extremely low shear forces. The device utilizes a benign vacuum sealing strategy for reversible application to pre-established cell cultures. We apply this device to an existing culture of breast cancer cells to demonstrate the negligible effect of its shear flow on migratory behavior. Lastly, we extend the stacked-flow design to demonstrate its scalable architecture with a prototype device for generating an array of combinatorial gradients.